Heat Phase Adjuster(HPA)を用いた熱音響システムの制御 ―エネルギー変換効率向上に向けた検討 - 森下, 大夢; 渡辺, 好章; 坂本, 眞一 (Thermal science and engineering, 2018)
In order to control resonance mode and improve the energy conversion efficiency of loop-tube-type thermoacoustic engines, we have proposed locally heating method, as called a Heat Phase Adjuster (HPA). In previous study, it is reported that using a HPA enables to improve the energy conversion efficiency of the loop-tube-type thermoacoustic system, and its efficiency depends on the input heat quantity of the HPA. However, the factor has not been clear. In this paper, the factor that improves the energy conversion efficiency of the thermoacoustic system using the HPA is experimentally investigated. Acoustic intensity and phase difference between sound pressure and particle velocity are calculated. And the increase in entropy flow through the prime mover stack is calculated. As the results, using the HPA shifts phase difference distribution between sound pressure and particle velocity. Also, using the HPA suppresses the increase in entropy flow through the prime mover stack. These results indicate that using a HPA can realize the more reversible energy conversion in the prime mover stack. These findings lead to the understanding of the factor that improves the energy conversion efficiency of the thermoacoustic system using the HPA.